Murine Norovirus: Propagation, Quantification, and Genetic Manipulation. Issue 1 (1st May 2014) - Hwang, Seungmin; Alhatlani, Bader; Arias, Armando; Caddy, Sarah L.; Christodoulou, Constantina; Bragazzi Cunha, Juliana; Emmott, Ed; Gonzalez‐Hernandez, Marta; Kolawole, Abimbola; Lu, Jia; Rippinger, Christine; Sorgeloos, Frédéric; et al.
Abstract: Murine norovirus (MNV) is a positive‐sense, plus‐stranded RNA virus in the Caliciviridae family. It is the most common pathogen in biomedical research colonies. MNV is also related to the human noroviruses, which cause the majority of nonbacterial gastroenteritis worldwide. Like the human noroviruses, MNV is an enteric virus that replicates in the intestine and is transmitted by the fecal‐oral route. MNV replicates in murine macrophages and dendritic cells in cells in culture and in the murine host. This virus is often used to study mechanisms in norovirus biology, because human noroviruses are refractory to growth in cell culture. MNV combines the availability of a cell culture and reverse genetics system with the ability to study infection in the native host. Herein, we describe a panel of techniques that are commonly used to study MNV biology. Curr. Protoc. Microbiol 33:15K.2.1‐15K.2.61. © 2014 by John Wiley & Sons, Inc.